Effect of conscious anesthesia with remifentanil versus general anesthesia with propofol on embryo quality and pregnancy rate in ICSI (Journal of Pharmaceutical Negative Results, 2022)
Background: Anesthesia is a corner of stone in invitro fertilization method for infertile couple and can be detrimental on the any results of reproduction due to potential toxici-ty run into by the anesthetic medications used. Objective: To assess the effect of con-scious anesthesia with remifentanil versus general anesthesia with propofol on embryo quality and pregnancy rate in ICSI. Material and methods: Comparative cross-sectional study that’s enrolled Seventy infertile female who were enduring intra cyto-plasm sperm injection technique (ICSI) at the infertility center of High Institute for In-fertility Diagnosis and Assisted Reproductive Technique /Al-Nahrain University / Baghdad / Iraq, during a period from November 2021 until May 2022. The present study enrolled Seventy infertile females undergoing ICSI cycles with an age range of 19 to 40 years and an infertility duration ranging from 2 years to 10 years.Results: Mean level of day of embryo transferred was 2.5± 0.662 in conscious group and 2.59± 0.56 in GA group with no significant difference (p=0.5), mean of number of embryos transferred was 2.9± 0.995 in conscious group and 2.78± 0.706 in GA group with no significant difference (p=0.5), and grade of embryo transferred mean level was 1.67± 0.685 in conscious group and 1.52± 0.601 in GA group with no sig-nificant difference (p=0.3). Pregnancy in conscious group happened in 13 (37.1%) and 12 (34.3%) of patients in GA group.Conclusion: Conscious anesthesia remifentanil with had better reproductive outcome on fertilization rate cleavage and grade 1 embryo rate with significant higher pregnancy rate than general anesthesia with propofol.